The Interventional Effects of Tubson-2 Decoction on Ovariectomized Rats as Determined by a Combination of Network Pharmacology and Metabolomics - Yang, Fan; Dong, Xin; Ma, Feixiang; Xu, Feng; Liu, Jie; Lu, Jingkun; Li, Chunyan; Bu, Ren; Xue, Peifeng (Frontiers in Pharmacology, 2020)
Post-menopausal osteoporosis (PMOP) is associated with estrogen deficiency and worldwide, is becoming increasingly more prevalent in aging women. Various anti-PMOP drugs have been developed to reduce the burden of PMOP; generally, these drugs are efficacious, but with some adverse side effects. Tubson-2 decoction (TBD), a popular traditional Mongolian medicine, has been used to treat PMOP for centuries. However, the precise mechanisms underlying the action of TBD on PMOP have yet to be fully elucidated. Herein, we combined network pharmacology with untargeted metabolomics to identify the key targets and metabolic pathways associated with the interventional effects of TBD on ovariectomized (OVX) rats. Furthermore, we investigated the bone histomorphometry of eight different groups of rats to evaluate the therapeutic effect of TBD. First, we established a TBD-target/PMOP network via network pharmacology; this network identified three key protein targets—vitamin D receptor (VDR), cytochrome P450 19A1 (CYP19A1), and 11β-hydroxysteroid dehydrogenase type 1 (HSD11B1). Morphological analysis showed that severe impairment of the bone micro-architecture in OVX rats could be improved by TBD administration. The TBD-treated rats had a significantly lower bone surface-to-tissue volume (BS/TV) and a significantly smaller trabecular separation (Tb·Sp.) (P<0.05) than the OVX rats; in contrast, bone volume fraction (BVF), trabecular thickness (Tb·Th.), trabecular number (Tb·N.), and bone mineral density (BMD) were significantly higher in the TBD-treated rats (P<0.05). Multivariate and univariate analysis showed that OVX resulted in significant alterations in the concentrations of 106 metabolites and 26 metabolic pathways (P<0.05); in addition, 40 potential biomarkers were identified to investigate the progression of PMOP. Network pharmacology showed that major alterations in vitamin B6 metabolism were associated with the VDR target. Next, we validated the three crucial targets (VDR [P<0.01], HSD11B1 [P<0.01], and CYP19A1 [P<0.05]) by ELISAs and demonstrated that the levels of these targets were elevated in the OVX group but reduced in the TBD-treatment group. Collectively, our results suggest that the interventional effects of TBD on OVX rats are likely to be associated with the down regulation of VDR. Our findings enhance our molecular understanding of the interventional effects of TBD on PMOP and will allow us to develop further TBD studies.